Working while incapable to work? Changing concepts of permitted work in the UK disability benefit system - Jackie Gulland (Disability Studies Quarterly, 2017)
This article focusses on the borderland between "work" and "not work" in UK disability benefit systems. People who claim disability benefits often have to prove that they are "incapable of work" in order to qualify. The idea of incapacity for work requires an understanding of the meaning of the term "work," a concept which has a common sense simplicity but which is much more difficult to define in practice. UK disability benefit systems have developed the notion of "permitted work" to allow people to do small amounts of paid work while retaining entitlement to benefit. This concept of "permitted work" has its roots in the early twentieth century when claimants were sometimes entitled to disability benefits if any work that they did was considered to be sufficiently trivial to not count as "work." Policy on this changed over time, with particular developments after the Second World War, as rehabilitation and therapy became the key focus of permitted work rules. Current developments in UK social security policy treat almost everyone as a potential worker, changing the way in which permitted work operates. This article uses archive material on appeals against refusals of benefit, policy documents and case law to consider the social meanings of these moving boundaries of permitted work. Disability benefits are not value neutral: they are measures of social control which divide benefit claimants into those who are required to participate in the labour market and those who are exempted from this requirement.
Keywords: Work; disability benefits; social insurance; twentieth-century history; United Kingdom; universal credit